Production of juçara mead: Physicochemical characteristics and sensory acceptance (Research, Society and Development, 2025)
In this study, we aimed to produce mead using juçara pulp during the fermentation process and evaluate its chemical, physicochemical, and sensory characteristics. An experimental, laboratory-based, qualitative, and quantitative study was conducted with statistical support. Mead is a fermented beverage made from honey. In this study, mead was produced with the addition of juçara pulp (Euterpe edulis), a native Brazilian fruit that is currently endangered. The must was adjusted to 27 °Brix and fermented with Saccharomyces bayanus (0.37 g·L⁻¹). On the 21st day, 10% juçara pulp was added to enhance the product both functionally and sensorially. The mead was analyzed for pH, total titratable acidity, alcohol content, dry extract, moisture, total soluble solids, turbidity, total monomeric anthocyanins, and antioxidant activity (ABTS). After 41 days, cold clarification was carried out, followed by bottling and storage at 3 °C. The mead was analyzed for physicochemical and antioxidant parameters (ABTS) and evaluated sensorially using the just-about-right (JAR) test. The results met Brazilian legislation, with notable antioxidant activity (2.44 µmol·g⁻¹ Trolox) and 14.48 mg·L⁻¹ of anthocyanins. Sensorially, the product showed good acceptance, with 78% approval.